An investigation of visual, spatial and visual-spatial working memory, attention and learning in dyslexic children - Allman, Justin J. (Trinity College (Dublin, Ireland). School of Psychology, 2007)
This dissertation investigated dyslexic children's functioning on a range of visual, spatial and visuospatial (VS), working memory (WM), attentional and learning tasks. Within the existing research which has touched upon these areas, there is a lack of consensus in respect to the level (if any) of impaired functioning in dyslexic children, or how these impairments should be conceptualised in relation to these cognitive abilities. The six experimental chapters presented in this thesis through a systematic and multidimensional approach to assessment, have attempted to offer further clarity in our understanding of dyslexic functioning across these cognitive abilities.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin